The Incredible Harvest Excursion of 1908 - Cherwinski, W. J. C. (Walter Joseph Carl) (Labour / Le Travail, 1980)
To satisfy the continuing need for agricultural labour in western Canada, especially at harvest time, the CPR after 1890 ran cheap harvest excursions from Eastern and central Canada each August and September. Accordingly, to insure an adequate supply of workers and potential settlers the railway companies, together with the federal and provincial governments, created an image of the prairies as a land of opportunity offering plentiful jobs at high wages. Owing to a variety of factors, however, unprecedented numbers responded to the 1908 appeal causing unexpected problems for all concerned. Some of those in the Maritime contingent were particularly troublesome as, bored and thirsty, they went on a rampage which touched most of the communities on the Main Line from Chalk River to Winnipeg. Once in the West distribution problems plagued all the excursionists with the result that places like Winnipeg, Moose Jaw, and Regina had too many harvesters on hand, while other places faced shortages. Consequently, numerous men wandered about aimlessly looking for work and often were forced to accept alternate employment at substantially less money than they had expected. The result was that the image of the West as capable of satisfying all those who went there in search of work was temporarily tarnished.